Building Buzz: (Scientists) Communicating Science in New Media Environments. (December 2014) - Liang, Xuan; Su, Leona Yi-Fan; Yeo, Sara K.; Scheufele, Dietram A.; Brossard, Dominique; Xenos, Michael; Nealey, Paul; Corley, Elizabeth A.
Public communication about science faces novel challenges, including the increasing complexity of research areas and the erosion of traditional journalistic infrastructures. Although scientists have traditionally been reluctant to engage in public communication at the expense of focusing on academic productivity, our survey of highly cited U.S. nano-scientists, paired with data on their social media use, shows that public communication, such as interactions with reporters and being mentioned on Twitter, can contribute to a scholar's scientific impact. Most importantly, being mentioned on Twitter amplifies the effect of interactions with journalists and other non-scientists on the scholar's scientific impact.